Delayed periorbital hemorrhage in oculoplastic surgery patients on oral anticoagulants. (4th March 2021) - Wagner, Lilly H.; Bradley, Elizabeth A.; Giese, Isaiah; Mehta, Viraj J.; Seiff, Stuart R.
ABSTRACT: Periorbital hemorrhage is a potentially sight threatening surgical complication. The effect of new oral anticoagulants (NOACs) on hemorrhagic events after periorbital surgery has not been investigated. We describe four cases of severe delayed postoperative hemorrhage associated with NOACs, in addition to three cases in patients on traditional antithrombotic agents. Time of delayed hemorrhage ranged from postoperative day 2 to 6. Six patients required surgical intervention to achieve control of bleeding, and two patients required transfusion of blood products. Risk factors and management of this rare complication are discussed.